APERSEPSI GURU TERHADAP MOTIVASI BELAJAR SISWA KELAS V PADA MATA PELAJARAN MATEMATIKA - Oktariani, Fajar; Subiyanto, Subiyanto; Mahardika, Astuti (Universitas Muhammadiyah Magelang, 2015)
This study aimed to find out the correlation between apperception with learning motivation. 46 fifth graders were considered as the population. This study employed total population sampling method which involved examining the entire population of interest. The data were collected through questionnaire, interview, and observation. The variables were the apperception performed by the teachers (X) and the student’s learning motivation (Y). Product-Moment Correlation was used to analyze the data and performed using SPSS Version 16.0. The result revealed that there was correlation between apperception and student’s learning motivation with the Pearson’s r value of 0.685 and strong positive correlation between the two variables with the sig. value of 0.00<0.005. The apperception performed by the teacher contributed 47% of student’s learning motivation while 53% were influenced by other factors.